PENERAPAN EVALUASI RINGKAS, RAPI, RESIK, RAWAT, RAJIN PT. INKA (PERSERO) MADIUN - Rio Surya Christian (The Indonesian Journal of Occupational Safety and Health, 2018)
Sort, Set, Shine, Standardize, and Sustain (5S) program is an attempt to minimize or eliminate harm by creating a good workplace culture in the workplace. A comfortable working environment will improve efficiency, productivity, quality, and safety. The 5S program is one of the administrative controls used to prevent accidents. 5S implementation will be reached and applied with support from all sides involved, start from top management, middle management, and low management. The study aims to evaluate the application of 5S in PT. INKA (Persero) Madiun. This study was observational and descriptive research using cross sectional design. The results showed that the application of 5S at PT. INKA (Persero)Madiun had been done since the first time but there wasn’t 5S activity. In 2014, the company's policy on 5R implementation appear so that the 5S implementation was fully supported by the company. Evaluation of the 5S implementation involves 5 areas include open area and workshop area, that already apply 5S well. The conclusions of this study was implementation 5S at PT. INKA (Persero) Madiun need to increase and support from top level management. Keywords: set, shine, sort, standardize, sustain